Drug‐resistant tuberculosis: An update on disease burden, diagnosis and treatment. Issue 7 (11th April 2018) - Lange, Christoph; Chesov, Dumitru; Heyckendorf, Jan; Leung, Chi C.; Udwadia, Zarir; Dheda, Keertan
ABSTRACT: The emergence of antimicrobial resistance against Mycobacterium tuberculosis, the leading cause of mortality due to a single microbial pathogen worldwide, represents a growing threat to public health and economic growth. The global burden of multidrug‐resistant tuberculosis (MDR‐TB) has recently increased by an annual rate of more than 20%. According to the World Health Organization approximately only half of all patients treated for MDR‐TB achieved a successful outcome. For many years, patients with drug‐resistant tuberculosis (TB) have received standardized treatment regimens, thereby accelerating the development of MDR‐TB through drug‐specific resistance amplification. Comprehensive drug susceptibility testing (phenotypic and/or genotypic) is necessary to inform physicians about the best drugs to treat individual patients with tailor‐made treatment regimens. Phenotypic drug resistance can now often, but with variable sensitivity, be predicted by molecular drug susceptibility testing based on whole genome sequencing, which in the future could become an affordable method for the guidance of treatment decisions, especially in high‐burden/resource‐limited settings. More recently, MDR‐TB treatment outcomes have dramatically improved with the use of bedaquiline‐based regimens. Ongoing clinical trials with novel and repurposed drugs will potentially further improve cure‐rates, and may substantially decrease the duration of MDR‐TB treatment necessary to achieve relapse‐free cure.